Sharia Economics on the Market Relocation Policy of Street Vendors in Purbalingga Food Center: Socio-Economic Conditions as the Consideration - Azizah, Nisrina; Faozan, Akhmad (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research investigates the impact of market relocation on the socio-economic conditions of street vendors at the Purbalingga Food Center (PFC). The relocation policy aimed to discipline street vendors, create a more representative culinary area, and address urban issues by establishing a new crowd center in the Purbalingga district. The study employs descriptive qualitative research methods, incorporating interviews, observation, and documentation for data collection. The findings reveal several outcomes: sustained positive interaction among traders, increased comfort due to improved facilities, enhanced security, decreased income for street vendors resulting from a lack of buyers, and the emergence of new business opportunities such as parking attendants and cleaning staff. Despite the income decline, the relocation brought overall benefits, aligning with Sharia economic principles. The study concludes that the government's relocation policy, while introducing challenges, ultimately generated advantages for both traders and policymakers. The results highlight the multifaceted impact of such policies, emphasizing the need for careful consideration and alignment with existing issues to maximize benefits for all stakeholders.